Index of winter severity and its regional variation in Finland - Mansikkaniemi, Hannu (Geographical Society of Finland, 1979)
Winter is considered as an environmental stress that hinders human activity and also makes heavy economic demands. An index of winter severity (Ws) is introduced, based on the following indicators: heating requirement (Hr, day degrees, limit < +12°C), number of hard frosty days (Tmd, limit < ‑ 15°C), snow depth (Sdpt). quantity of snowfall (S), number of snowfall days (Sd, limit > 1 mm), wind speed (ws), number of strong wind days in winter (wMd, limit > 11 m/s), relative humidity (U) and maximum length of night (NiM). The heating requirement is regarded as important as all the other indicators together in the index. The severity of winter can also be measured roughly by a simplified method, Ws' index. The indices show that in spite of strong windchill on open islands winter is easiest in the SW archipelago in Finland as a result of high temperature and small snowfall. Inconveniences caused by winter are already seen on the S and SW coast, Helsinki–Turku–Pori area; they are 10–15 % greater than in Mariehamn. In rather a wide area, southwest of the line Helsinki–Tampere–Vaasa, the differences are only locally 25 % higher than in Mariehamn. Inland from the line the disadvantages of winter increase strongly, the indices for Jyvaskylä and Joensuu being 45‑5517c higherthan in Mariehamn. As a result of low temperature and very heavy snowfall the winter is most difficult in the Kuusarno area. The index is 92 % higher than in Mariehamn. In Central Lapland the corresponding difference is 85‑90 % and in southern Lapland and the Inari basin in northern Lapland about 80 %. – Winter is clearly easiest in the most densely populated area. This is a very favourable economic factor in Finland.